A Facile One-Pot Synthesis of Selenoureidopeptides Employing LiAlHSeH through Staudinger Aza-Wittig-Type Reaction - Basavaprabhu; Sharanabai, Kupendra M.; Prabhu, Girish; Panduranga, Veladi; Sureshbabu, Vommina V. (Synthesis, 2015)
A one-pot protocol for the synthesis of selenoureidopeptides employing lithium aluminum hydride hydroselenide (LiAlHSeH) as a selenating agent via a Staudinger aza-Wittig-type reaction is reported. The protocol involves the use of Nα-protected aminoalkyl azides and isothicyanato esters to afford the desired products in good yields. This protocol is a direct approach to the synthesis of selenourea compounds that avoids the synthesis of isoselenocyanates and does not require multistep synthesis.
Keywords: selenation; Staudinger aza-Wittig-type reaction; LiAlHSeH; selenoureidopeptide mimics